Politik Hukum Pembentukan Cyber Law Undang-Undang Informasi dan Transaksi Elektronik di Indonesia - Sherly Nelsa Fitri (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2022)
This legal research aims to find the influence of legal politics in the change of cyber law in Indonesia. This legal research is normative law research. The legal materials used are primary legal materials and secondary legal materials. That the politics of law is the basis of the state, as stated in the 1945 Constitution of the Republic of Indonesia, paragraph 4. Until now, there are two cyber laws (UU ITE) that have been and are or are still valid in Indonesia. The change of Cyberlaw (UU ITE) occurs because of the influence of political law that becomes the basic policy that determines the direction, form, and content of the law that will be formed by the needs of the state at the time of the law is in force and the politics of the interests of the government at the time the law is in force.